Gestão do conhecimento nas organizações: modelo conceitual centrado na cultura organizacional e nas pessoas - Moraes, Cássia Regina Bassan de [UNESP] (2010)
Knowledge is created by persons, that is, an organization cannot create knowledge itself without the persons that compose it. Thus, to have the focus in the knowledge creation, it has that to search the development of the collaborators. In this scenery, this research questions the difficulty of studying the behavior and the professional attitudes of the persons involved in the process of Knowledge Management in organizations, considering the existence of subjective and complex elements, by involving the deal with people. As hypothesis, it has been estimated that a Conceptual Model, based in the Organizational Culture and the People Management, can contribute to the Knowledge Management in organizations. In this way, this study objectives the construction of a Conceptual Model, based in the Organizational Culture and the People Management, based on Soft System Methodology, aiming to minimize the obstacles for the implantation of Knowledge Management in the organizations. As specific objectives, this study aimed to analyze Organizational Culture, Human Behavior and Knowledge Management concepts; adopt the Soft System Methodology at organizational environment; propose a Conceptual Model, based in the Organizational Culture and the People Management; validate the Conceptual Model at a food business organization. As result, a Conceptual Model for the Knowledge Management centered in the Organizational Culture and the People was build, which was validated in an organization of the São Paulo State by the application of the Soft System Methodology seven steps. It can be concluded that Soft System Methodology application was able to generate a Conceptual Model, which provided changes suggestions to the organization on Knowledge Management